Effect of jet grout slab on factor of safety for deep excavation - Tan, Siong Wei (2018)
This report is a study on the use Jet Grout Slab for deep excavation. In this study, finite element analysis is carried out to examine how the different types of retaining wall, thickness of jet grout, excavation width as well as different properties of both the retaining wall and jet grout, will have an effect on the basal heave Factor of Safety (FSFE) and the horizontal wall displacement. In addition, comparisons are carried out between the factor of safety from finite element analysis and conventional methods such as Eide et al. (1972) and modified Terzaghi (Wong & Goh 2002). The software that will be used is the two dimensional finite element program PLAXIS 2D. The results show that the Factor of Safety for diaphragm wall and sheetpile wall are similar and both show a positive correlation with thickness of jet grout used. The horizontal displacement of the sheetpile wall is always larger than the diaphragm wall, however the rate of increase differs between the two walls. The increase in the JGP-wall adhesion factor (aJ) will result in a higher factor of safety. The factor of safety computed from the Eide et al (1972) method is lower than the PLAXIS 2D while that from Wong & Goh (2002) is the highest among the three.